Musn't grumble: Immigration, health and health service use in the UK and Germany - Jonathan Wadsworth (Institute for the Study of Labor (IZA), 2012)
A rise in population caused by increased immigration is sometimes accompanied by concerns that the increase in population puts additional or differential pressure on welfare services which might affect the net fiscal contribution of immigrants. The UK and Germany have experienced significant increases in immigration in recent years and this study uses longitudinal data from both countries to examine whether immigrants differ in their use of health services than native born individuals on arrival and over time. While immigrants to Germany, but not the UK, are more likely to self-report poor health than the native-born population, the samples of immigrants use hospital and GP services at broadly the same rate as the native born populations in both countries. Controls for observed and unobserved differences between immigrants and native-born sample populations make little difference to these broad findings.
Keywords: H00; J00; 330; immigration; health; health service; Einwanderung; Migranten; Gesundheitsversorgung; Nachfrage; Deutschland; Großbritannien